Краткое Видео Как Средство Формирования Национальной Идентичности В Современном Китае (Short Video as a Tool of Forming National Identity in Contemporary China) - Ruiqi, Hu; Muzykant, Valerii L. (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
Nowadays, social media plays an vitally important role in the transmission and exchange of data around the world, and China is certainly no exception. Short video platforms have gained particular popularity among social media in recent years. In this regard, we have conducted a study that provides insight into how Chinese short video platforms can be a tool for building national identity in the era of social media in China. As a result of the analysis, it was noted that short videos play an important role in shaping a sense of national identity in modern China. Short videos as a tool for the formation of national identity were considered on the example of the Douyin service. On Douyin, the formation of national identity is reflected in videos with the hashtag